Enhancing Learning through Formative Assessment and Feedback. - Irons, Alatair (Routledge, 2022)
Assessment is a critical aspect of higher education because it has a range of powerful impacts on what staff and students do and how universities operate. Underpinned by relevant theory and practical advice this fully updated new edition takes into account the changing expectation of students in the context of an increasingly complex and shifting higher education environment to promote the role of formative assessment and formative feedback and its impact on shaping the student learning experience.